2005
DOI: 10.1101/lm.98305
|View full text |Cite
|
Sign up to set email alerts
|

Lack of the metabotropic glutamate receptor subtype 7 selectively modulates Theta rhythm and working memory

Abstract: Metabotropic glutamate receptors (mGluRs) are known to play a role in synaptic plasticity and learning. We have previously shown that mGluR7 deletion in mice produces a selective working memory (WM) impairment, while other types of memory such as reference memory remain unaffected. Since WM has been associated with Theta activity (6-12 Hz) in EEGs, and since EEG abnormalities have been observed in these mice before, we studied the effect of mGluR7 gene ablation on EEG activity in the hippocampus, in particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Nevertheless, recent studies revealed that theta activity in hippocampus was increased in mGluR7 Ϫ/Ϫ mice and that this alteration of rhythmic activity was associated with the working memory defect (Holscher et al, 2005). It has been demonstrated that increases in the amygdalohippocampal area also coincide with fear conditioning and expression of anxiety and fear-related responses (Seidenbecher et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, recent studies revealed that theta activity in hippocampus was increased in mGluR7 Ϫ/Ϫ mice and that this alteration of rhythmic activity was associated with the working memory defect (Holscher et al, 2005). It has been demonstrated that increases in the amygdalohippocampal area also coincide with fear conditioning and expression of anxiety and fear-related responses (Seidenbecher et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Performances in complex working memory tasks such as 8-arm radial maze task were also impaired in mGluR7 knockout mice [133]. Interestingly, the working memory deficit was associated with an increased hippocampal theta power while performing the task, which was suggested to reflect a lack of modulation of local inhibition, in turn leading to decreased neuronal firing threshold and altered spike timing [134]. At the cellular level, mGluR7 knockout mice were reported to exhibit deficits in short-term, but not long-term potentiation in the hippocampus [135], findings in agreement with the hypothesis that short-term potentiation represents the cellular substrate for short-term memory and critical for working memory performances.…”
Section: Schizophreniamentioning
confidence: 99%
“…For example, electrophysiological studies with rodents have demonstrated that WM performance is correlated with both the magnitude of long-term depression in the hippocampus (Nakao et al, 2002) and the theta rhythm in the hippocampus (Holscher et al, 2005). A rodent pharmacological study showed that WM impairment was accompanied by the deposition of Amyloid beta-peptide (Abeta) in the hippocampus (Leighty et al, 2004).…”
Section: Introductionmentioning
confidence: 99%